(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare the effects of different surface finishing treatments applied to two different CAD/CAM materials on the color stability after thermal aging with coffee and cola.Materials and Methods: Polymerized resin nanoceramic (LAVA Ultimate, LU) and lithium disilicate glass-ceramic (IPS e.max CAD, EC) were examined in the study. The samples with A1 HT color at a size of 14 x 12 mm and a thickness of 0.5 ± 0.05 mm were prepared from these ceramic materials (N=144). Color measurement of each specimen was calculated with a spectrophotometer using color parameters on a gray backing between baseline color, polishing/glazing and after 5000 cycles of coffee and cola thermocycling. ANOVA and the Fisher’s LSD test were used for testing statistical significance (p 0.05).Results: LU exhibited higher color change values than EC after thermal aging. In the EC group, glazing provided statistically different results as compared to the manual and control groups (p 0.05). The lowest color change for all stages was observed in IPS e.max CAD ceramics that were treated by glazing.Conclusion: In terms of color stability, glazing can be recommended for EC, and manual polishing as an alternative to glazing for LU.Keywords: CAD/CAM; ceramics; prosthodontics.